Corrosion-resistant pervious concrete
By adding phosphorus slag powder, rosin, paraffin particles and other components to the concrete, combined with the aggregate ratio and the use of polyurethane resin, corrosion-resistant and water-permeable concrete with good corrosion-resistant and water-permeable properties is prepared, which solves the problem of insufficient performance of traditional concrete in harsh environments and achieves efficient corrosion-resistant and water-permeable effects.
Patent Information
- Application Number
- CN202411762344.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-28
AI Technical Summary
Traditional concrete has problems such as decreased strength, increased cracks and insufficient durability in harsh environments and chemical erosion. Its corrosion resistance and water permeability are insufficient, making it difficult to meet the use under high load conditions.
A corrosion-resistant and water-permeable concrete is used to prepare concrete with good corrosion-resistant and water-permeable properties by adding components such as phosphorus slag powder, rosin, paraffin particles, and combined with the selection and ratio of aggregates, as well as the addition of polyurethane resin and inorganic nanocomposite adhesive.
The concrete effectively resists the erosion of various corrosive substances, extends its service life, and has good water permeability, reduces urban flooding and improves the ecological environment. It also has high compressive strength and flexural strength, and can withstand the test of various harsh environments.
Smart Images

Figure CN119528499A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, in particular to a corrosion-resistant permeable concrete. Background Art
[0002] With the acceleration of urbanization, the construction of urban infrastructure faces more and more challenges. Among them, traditional concrete materials often suffer from problems such as reduced strength, increased cracks and insufficient durability when facing harsh environmental conditions and frequent chemical erosion. These problems not only increase the cost of maintenance and repair, but also shorten the service life of concrete structures, affecting public safety and economic benefits.
[0003] However, traditional concrete materials have poor corrosion resistance, especially when exposed to salt water, acid and alkali solutions and other corrosive media, which can easily lead to fatal problems such as steel corrosion and concrete spalling. Conventional protective measures mostly rely on surface coatings. Although these measures can provide protection in the short term, the coatings are easy to fall off and difficult to maintain over time, and cannot fundamentally solve the corrosion resistance problem of concrete. In urban areas with high water content or frequent rainfall, traditional concrete has poor permeability, which can easily lead to rainwater accumulation on the ground, forming puddles or waterlogging. This not only increases the pressure on the urban drainage system, but also harms the urban ecological environment. Despite the emergence of permeable concrete, its strength and durability are often not guaranteed, and it is difficult to adapt to use under high load conditions.
[0004] To this end, technicians in this field have proposed a corrosion-resistant permeable concrete, aiming to improve the comprehensive performance of concrete and promote the sustainable development of urban construction. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a corrosion-resistant permeable concrete to solve the problems raised in the background technology.
[0006] A corrosion-resistant permeable concrete is prepared from the following raw materials in parts by weight: 100-300 parts of cement, 200-400 parts of aggregate, 10-20 parts of phosphorus slag powder, 3-5 parts of rosin, 5-10 parts of paraffin particles, 5-10 parts of inorganic nano-composite adhesive, 5-10 parts of polyurethane resin, 2-5 parts of epoxy resin coating, 1-3 parts of micro-pigment, 40-60 parts of water and 0.5-1 part of water reducing agent.
[0007] Preferably, the corrosion-resistant permeable concrete is prepared from the following raw materials in parts by weight: 100 parts of cement, 250 parts of aggregate, 15 parts of phosphorus slag powder, 4 parts of rosin, 7 parts of paraffin particles, 7 parts of inorganic nano-composite adhesive, 7 parts of polyurethane resin, 3 parts of epoxy resin coating, 2 parts of micro-pigment, 50 parts of water, and 0.5 parts of water reducer.
[0008] Preferably, the aggregate includes coarse aggregate and fine aggregate, the coarse aggregate includes brick pottery or crushed stone, the fine aggregate is expanded perlite or pumice, and the ratio of the coarse aggregate to the fine aggregate is 70:30.
[0009] Preferably, the method for preparing the corrosion-resistant permeable concrete comprises the following steps:
[0010] S1. Using brick pottery and expanded perlite as aggregates, mixing them in a ratio of 70:30 and washing them to remove impurities and dust to obtain an aggregate premix;
[0011] S2, putting cement, phosphorus slag powder, rosin and micro-pigment into a dry mixer for preliminary mixing, then putting the aggregate premix into it, using a forced mixer or a concrete mixer, mixing it for the first time, so that all the raw materials are fully combined and no dry powder particles remain, and then evenly sprinkle the paraffin particles into it to obtain a dry mixture;
[0012] S3, respectively, slowly and evenly pour the polyurethane resin into the dry mixture, use a forced mixer to stir for the second time, the polyurethane resin and the dry mixture are fully combined, after obtaining a combination, pour the water reducer into the water and stir evenly, and then add it into the combination twice;
[0013] S4, using a forced mixer to stir for a third time for 3 to 5 minutes until a uniform mixture without dry powder is obtained;
[0014] S5. Pour the uniformly mixed mixture into a mold and gently vibrate to release the air so that the mixture fully fills the mold;
[0015] S6. After forming, the mixture is cured in a low temperature and humid environment for 7-14 days. After the mixture is completely hardened, surface treatment is performed and a layer of epoxy resin coating is sprayed on the surface to finally obtain corrosion-resistant permeable concrete.
[0016] Preferably, when cement, phosphorus slag powder, rosin and micro-pigment are put into a dry mixer for preliminary mixing, the mixing time is 1-2 minutes until the color is uniform.
[0017] Preferably, when the forced mixer is used for the first stirring, the stirring time is controlled within 3 to 5 minutes, and after the stirring is completed, the dry mixture has a uniform color, no stratification, and no obvious lumps.
[0018] Preferably, the polyurethane resin is slowly and evenly poured into the dry mixture, and the second stirring is performed using a forced mixer for 2 to 3 minutes.
[0019] Preferably, the water reducing agent is first poured into water and stirred evenly, and then added into the combination in two portions, 70% is added for the first time, the consistency is observed, and then the remaining water is gradually added.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. By adding phosphorus slag powder, rosin, paraffin particles and other ingredients, the concrete can effectively resist the erosion of various corrosive substances and extend its service life. The selection and proportion of aggregates, as well as the addition of polyurethane resin and inorganic nano-composite adhesive, make the concrete have good water permeability, which helps to reduce urban waterlogging and improve the ecological environment.
[0022] 2. The present invention not only reduces resource waste but also contributes to environmental protection by utilizing industrial waste such as phosphorus slag powder; in addition, the preparation process of the concrete is relatively simple, with low energy consumption, and through scientific proportioning and preparation technology, the concrete has high compressive strength and flexural strength, and at the same time has good durability and can withstand the test of various harsh environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The present invention is a flow chart of the corrosion-resistant permeable concrete. DETAILED DESCRIPTION
[0024] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0025] As attached Figure 1 As shown:
[0026] Embodiment 1: The present invention provides a corrosion-resistant permeable concrete, which is prepared from the following raw materials in parts by weight: 100 parts of cement, 200 parts of aggregate, 10 parts of phosphorus slag powder, 3 parts of rosin, 5 parts of paraffin particles, 5 parts of inorganic nano-composite adhesive, 5 parts of polyurethane resin, 2 parts of epoxy resin coating, 1 part of micro-pigment, 40 parts of water, and 0.5 parts of water reducer.
[0027] The aggregate includes coarse aggregate and fine aggregate. The coarse aggregate includes brick pottery or crushed stone, and the fine aggregate is expanded perlite or pumice. The ratio of the coarse aggregate to the fine aggregate is 70:30.
[0028] The preparation method of corrosion-resistant permeable concrete is as follows:
[0029] S1. Using brick pottery and expanded perlite as aggregates, mixing them in a ratio of 70:30 and washing them to remove impurities and dust to obtain an aggregate premix;
[0030] S2, putting cement, phosphorus slag powder, rosin and micro-pigment into a dry mixer for preliminary mixing, then putting the aggregate premix into it, using a forced mixer or a concrete mixer, mixing it for the first time, so that all the raw materials are fully combined and no dry powder particles remain, and then evenly sprinkle the paraffin particles into it to obtain a dry mixture;
[0031] S3, respectively, slowly and evenly pour the polyurethane resin into the dry mixture, use a forced mixer to stir for the second time, the polyurethane resin and the dry mixture are fully combined, after obtaining a combination, pour the water reducer into the water and stir evenly, and then add it into the combination twice;
[0032] S4, using a forced mixer to stir for a third time for 3 to 5 minutes until a uniform mixture without dry powder is obtained;
[0033] S5. Pour the uniformly mixed mixture into a mold and gently vibrate to release the air so that the mixture fully fills the mold;
[0034] S6. After forming, the mixture is cured in a low temperature and humid environment for 7-14 days. After the mixture is completely hardened, surface treatment is performed and a layer of epoxy resin coating is sprayed on the surface to finally obtain corrosion-resistant permeable concrete.
[0035] When cement, phosphorus slag powder, rosin and micro pigment are put into a dry mixer for preliminary mixing, the mixing time is 1-2 minutes until the color is uniform.
[0036] When the forced mixer is used for the first stirring, the stirring time is controlled within 3 to 5 minutes, and after the stirring is completed, the dry mixture has a uniform color, no stratification, and no obvious lumps.
[0037] Pour the polyurethane resin slowly and evenly into the dry mixture, and use a forced mixer for the second stirring for 2 to 3 minutes.
[0038] Pour the water reducer into the water and stir evenly, then add it into the combination twice, adding 70% for the first time, observe its consistency, and then gradually add the remaining water.
[0039] Embodiment 2: The present invention provides a corrosion-resistant permeable concrete, which is prepared from the following raw materials in parts by weight: 100 parts of cement, 250 parts of aggregate, 15 parts of phosphorus slag powder, 4 parts of rosin, 7 parts of paraffin particles, 7 parts of inorganic nano-composite adhesive, 7 parts of polyurethane resin, 3 parts of epoxy resin coating, 2 parts of micro-pigment, 50 parts of water, and 0.5 parts of water reducer.
[0040] The aggregate includes coarse aggregate and fine aggregate. The coarse aggregate includes brick pottery or crushed stone, and the fine aggregate is expanded perlite or pumice. The ratio of the coarse aggregate to the fine aggregate is 70:30.
[0041] The preparation method of corrosion-resistant permeable concrete is as follows:
[0042] S1. Using brick pottery and expanded perlite as aggregates, mixing them in a ratio of 70:30 and washing them to remove impurities and dust to obtain an aggregate premix;
[0043] S2, putting cement, phosphorus slag powder, rosin and micro-pigment into a dry mixer for preliminary mixing, then putting the aggregate premix into it, using a forced mixer or a concrete mixer, mixing it for the first time, so that all the raw materials are fully combined and no dry powder particles remain, and then evenly sprinkle the paraffin particles into it to obtain a dry mixture;
[0044] S3, respectively, slowly and evenly pour the polyurethane resin into the dry mixture, use a forced mixer to stir for the second time, the polyurethane resin and the dry mixture are fully combined, after obtaining a combination, pour the water reducer into the water and stir evenly, and then add it into the combination twice;
[0045] S4, using a forced mixer to stir for a third time for 3 to 5 minutes until a uniform mixture without dry powder is obtained;
[0046] S5. Pour the uniformly mixed mixture into a mold and gently vibrate to release the air so that the mixture fully fills the mold;
[0047] S6. After forming, the mixture is cured in a low temperature and humid environment for 7-14 days. After the mixture is completely hardened, surface treatment is performed and a layer of epoxy resin coating is sprayed on the surface to finally obtain corrosion-resistant permeable concrete.
[0048] When cement, phosphorus slag powder, rosin and micro pigment are put into a dry mixer for preliminary mixing, the mixing time is 1-2 minutes until the color is uniform.
[0049] When the forced mixer is used for the first stirring, the stirring time is controlled within 3 to 5 minutes, and after the stirring is completed, the dry mixture has a uniform color, no stratification, and no obvious lumps.
[0050] Pour the polyurethane resin slowly and evenly into the dry mixture, and use a forced mixer for the second stirring for 2 to 3 minutes.
[0051] Pour the water reducer into the water and stir evenly, then add it into the combination twice, adding 70% for the first time, observe its consistency, and then gradually add the remaining water.
[0052] Embodiment 3: The present invention provides a corrosion-resistant permeable concrete, which is prepared from the following raw materials in parts by weight: 200 parts of cement, 300 parts of aggregate, 10 parts of phosphorus slag powder, 3 parts of rosin, 5 parts of paraffin particles, 5 parts of inorganic nano-composite adhesive, 7 parts of polyurethane resin, 5 parts of epoxy resin coating, 1 part of micro-pigment, 40 parts of water, and 0.7 parts of water reducer.
[0053] The aggregate includes coarse aggregate and fine aggregate. The coarse aggregate includes brick pottery or crushed stone, and the fine aggregate is expanded perlite or pumice. The ratio of the coarse aggregate to the fine aggregate is 70:30.
[0054] The preparation method of corrosion-resistant permeable concrete is as follows:
[0055] S1. Using brick pottery and expanded perlite as aggregates, mixing them in a ratio of 70:30 and washing them to remove impurities and dust to obtain an aggregate premix;
[0056] S2, putting cement, phosphorus slag powder, rosin and micro-pigment into a dry mixer for preliminary mixing, then putting the aggregate premix into it, using a forced mixer or a concrete mixer, mixing it for the first time, so that all the raw materials are fully combined and no dry powder particles remain, and then evenly sprinkle the paraffin particles into it to obtain a dry mixture;
[0057] S3, respectively, slowly and evenly pour the polyurethane resin into the dry mixture, use a forced mixer to stir for the second time, the polyurethane resin and the dry mixture are fully combined, after obtaining a combination, pour the water reducer into the water and stir evenly, and then add it into the combination twice;
[0058] S4, using a forced mixer to stir for a third time for 3 to 5 minutes until a uniform mixture without dry powder is obtained;
[0059] S5. Pour the uniformly mixed mixture into a mold and gently vibrate to release the air so that the mixture fully fills the mold;
[0060] S6. After forming, the mixture is cured in a low temperature and humid environment for 7-14 days. After the mixture is completely hardened, surface treatment is performed and a layer of epoxy resin coating is sprayed on the surface to finally obtain corrosion-resistant permeable concrete.
[0061] When cement, phosphorus slag powder, rosin and micro pigment are put into a dry mixer for preliminary mixing, the mixing time is 1-2 minutes until the color is uniform.
[0062] When the forced mixer is used for the first stirring, the stirring time is controlled within 3 to 5 minutes, and after the stirring is completed, the dry mixture has a uniform color, no stratification, and no obvious lumps.
[0063] Pour the polyurethane resin slowly and evenly into the dry mixture, and use a forced mixer for the second stirring for 2 to 3 minutes.
[0064] Pour the water reducer into the water and stir evenly, then add it into the combination twice, adding 70% for the first time, observe its consistency, and then gradually add the remaining water.
[0065] Embodiment 4, the present invention provides a corrosion-resistant permeable concrete, which is prepared from the following raw materials in parts by weight: 300 parts of cement, 350 parts of aggregate, 20 parts of phosphorus slag powder, 5 parts of rosin, 10 parts of paraffin particles, 10 parts of inorganic nano-composite adhesive, 10 parts of polyurethane resin, 2 parts of epoxy resin coating, 3 parts of micro-pigment, 60 parts of water, and 1 part of water reducer.
[0066] The aggregate includes coarse aggregate and fine aggregate. The coarse aggregate includes brick pottery or crushed stone, and the fine aggregate is expanded perlite or pumice. The ratio of the coarse aggregate to the fine aggregate is 70:30.
[0067] The preparation method of corrosion-resistant permeable concrete is as follows:
[0068] S1. Using brick pottery and expanded perlite as aggregates, mixing them in a ratio of 70:30 and washing them to remove impurities and dust to obtain an aggregate premix;
[0069] S2, putting cement, phosphorus slag powder, rosin and micro-pigment into a dry mixer for preliminary mixing, then putting the aggregate premix into it, using a forced mixer or a concrete mixer, mixing it for the first time, so that all the raw materials are fully combined and no dry powder particles remain, and then evenly sprinkle the paraffin particles into it to obtain a dry mixture;
[0070] S3, respectively, slowly and evenly pour the polyurethane resin into the dry mixture, use a forced mixer to stir for the second time, the polyurethane resin and the dry mixture are fully combined, after obtaining a combination, pour the water reducer into the water and stir evenly, and then add it into the combination twice;
[0071] S4, using a forced mixer to stir for a third time for 3 to 5 minutes until a uniform mixture without dry powder is obtained;
[0072] S5. Pour the uniformly mixed mixture into a mold and gently vibrate to release the air so that the mixture fully fills the mold;
[0073] S6. After forming, the mixture is cured in a low temperature and humid environment for 7-14 days. After the mixture is completely hardened, surface treatment is performed and a layer of epoxy resin coating is sprayed on the surface to finally obtain corrosion-resistant permeable concrete.
[0074] When cement, phosphorus slag powder, rosin and micro pigment are put into a dry mixer for preliminary mixing, the mixing time is 1-2 minutes until the color is uniform.
[0075] When the forced mixer is used for the first stirring, the stirring time is controlled within 3 to 5 minutes, and after the stirring is completed, the dry mixture has a uniform color, no stratification, and no obvious lumps.
[0076] Pour the polyurethane resin slowly and evenly into the dry mixture, and use a forced mixer for the second stirring for 2 to 3 minutes.
[0077] Pour the water reducer into the water and stir evenly, then add it into the combination twice, adding 70% for the first time, observe its consistency, and then gradually add the remaining water.
[0078] In summary, the table is:
[0079]
[0080] The concrete obtained in Example 1 has moderate strength, but the overall strength is insufficient due to the low cement content; it has good water permeability and is suitable for drainage requirements; in terms of corrosion resistance, phosphorus slag powder and rosin provide certain corrosion resistance, but it is not enough to cope with extreme environments;
[0081] The concrete obtained in Example 2 has balanced strength, which is sufficient to meet general load requirements without excessively increasing material costs; in terms of water permeability, it can maintain good water permeability, ensuring that the concrete is effective in rainwater discharge and drainage functions; in terms of corrosion resistance, the reasonable use of phosphorus slag powder, rosin and polyurethane resin makes it have excellent corrosion resistance, and the concrete has good fluidity during pouring;
[0082] The concrete obtained in Example 3 has a higher strength than that in Example 1, but its water permeability is affected to some extent. In terms of water permeability, it is only suitable for gaps with low requirements. In terms of corrosion resistance, the corrosion resistance is enhanced compared with that in Example 1, but the proportion of the matched materials fails to better exert its characteristics, and its corrosion resistance is weaker than that in Example 2.
[0083] The concrete obtained in Example 4 has high strength and is suitable for bearing large loads, but its water permeability is greatly reduced. In terms of water permeability, its water permeability is poor and may cause water to be unable to be discharged smoothly, affecting its function; in terms of corrosion resistance, it has the best corrosion resistance, but due to insufficient water permeability, problems may occur during long-term use.
[0084] Therefore, the raw material components and preparation method of the corrosion-resistant permeable concrete in Example 2 are the best choice, which can comprehensively achieve the best performance in all aspects and is suitable for actual engineering needs.
[0085] Importantly, it should be noted that the construction and arrangement of the present application shown in a plurality of different exemplary embodiments are only exemplary. Although only a few embodiments are described in detail in this disclosure, it should be readily understood by those who refer to this disclosure that many modifications are possible (e.g., the size, scale, structure, shape and proportion of various elements, as well as parameter values (e.g., temperature, pressure, etc.), mounting arrangements, use of materials, color, directional changes, etc.) without substantially departing from the novel teachings and advantages of the subject matter described in the application. For example, the element shown as integrally formed can be composed of multiple parts or elements, the position of the element can be inverted or otherwise changed, and the nature or number or position of the discrete element can be changed or changed. Therefore, all such modifications are intended to be included in the scope of the present invention. The order or sequence of any process or method steps can be changed or reordered according to alternative embodiments. In the claims, any "device plus function" clause is intended to cover the structure described herein that performs the function, and is not only structurally equivalent but also equivalent structure. Without departing from the scope of the present invention, other replacements, improvements, changes and omissions can be made in the design, operating conditions and arrangement of the exemplary embodiments. Therefore, the invention is not limited to a specific embodiment, but extends to several modifications still falling within the scope of the appended claims.
[0086] Additionally, in order to provide a concise description of exemplary embodiments, all features of an actual embodiment (ie, those features that are not relevant to the best mode presently contemplated for carrying out the invention or those that are not relevant to implementing the invention) may not be described.
[0087] It should be understood that in the development of any actual implementation, as in any engineering or design project, numerous implementation-specific decisions may be made. Such a development effort may be complex and time-consuming, but for those of ordinary skill having the benefit of this disclosure, without undue experimentation, the development effort will be a routine task of design, fabrication, and production.
[0088] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A corrosion-resistant permeable concrete, characterized in that: The invention is prepared from the following raw materials in parts by weight: 100-300 parts of cement, 200-400 parts of aggregate, 10-20 parts of phosphorus slag powder, 3-5 parts of rosin, 5-10 parts of paraffin particles, 5-10 parts of inorganic nano composite adhesive, 5-10 parts of polyurethane resin, 2-5 parts of epoxy resin coating, 1-3 parts of micro pigment, 40-60 parts of water and 0.5-1 part of water reducing agent.
2. The corrosion-resistant permeable concrete according to claim 1, characterized in that: The corrosion-resistant permeable concrete is prepared from the following raw materials in parts by weight: 100 parts of cement, 250 parts of aggregate, 15 parts of phosphorus slag powder, 4 parts of rosin, 7 parts of paraffin particles, 7 parts of inorganic nano-composite adhesive, 7 parts of polyurethane resin, 3 parts of epoxy resin coating, 2 parts of micro-pigment, 50 parts of water, and 0.5 parts of water reducer.
3. The corrosion-resistant permeable concrete according to claim 1, characterized in that: The aggregate includes coarse aggregate and fine aggregate. The coarse aggregate includes brick pottery or crushed stone, and the fine aggregate is expanded perlite or pumice. The ratio of the coarse aggregate to the fine aggregate is 70:
30.
4. The corrosion-resistant permeable concrete according to claim 1, characterized in that: The preparation method of the corrosion-resistant permeable concrete comprises the following steps: S1. Using brick pottery and expanded perlite as aggregates, mixing them in a ratio of 70:30 and washing them to remove impurities and dust to obtain an aggregate premix; S2, putting cement, phosphorus slag powder, rosin and micro-pigment into a dry mixer for preliminary mixing, then putting the aggregate premix into it, using a forced mixer or a concrete mixer, mixing it for the first time, so that all the raw materials are fully combined and no dry powder particles remain, and then evenly sprinkle the paraffin particles into it to obtain a dry mixture; S3, respectively, slowly and evenly pour the polyurethane resin into the dry mixture, use a forced mixer to stir for the second time, the polyurethane resin and the dry mixture are fully combined, after obtaining a combination, pour the water reducer into the water and stir evenly, and then add it into the combination twice; S4, using a forced mixer to stir for a third time for 3 to 5 minutes until a uniform mixture without dry powder is obtained; S5. Pour the uniformly mixed mixture into a mold and gently vibrate to release the air so that the mixture fully fills the mold; S6. After forming, the mixture is cured in a low temperature and humid environment for 7-14 days. After the mixture is completely hardened, surface treatment is performed and a layer of epoxy resin coating is sprayed on the surface to finally obtain corrosion-resistant permeable concrete.
5. The corrosion-resistant permeable concrete according to claim 4, characterized in that: When cement, phosphorus slag powder, rosin and micro-pigment are put into a dry mixer for preliminary mixing, the mixing time is 1-2 minutes until the color is uniform.
6. The corrosion-resistant permeable concrete according to claim 5, characterized in that: When the forced mixer is used for the first stirring, the stirring time is controlled within 3 to 5 minutes, and after the stirring is completed, the dry mixture has a uniform color, no stratification phenomenon, and no obvious lumps.
7. The corrosion-resistant permeable concrete according to claim 4, characterized in that: The polyurethane resin is slowly and evenly poured into the dry mixture, and the forced mixer is used for the second stirring, and the stirring time is 2 to 3 minutes.
8. The corrosion-resistant permeable concrete according to claim 4, characterized in that: The water reducer is first poured into water and stirred evenly, and then added into the combination in two portions, 70% is added for the first time, and its consistency is observed, and then the remaining water is gradually added.